The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/suco.201500022
|View full text |Cite
|
Sign up to set email alerts
|

Economic and human safety reliability levels for existing structures

Abstract: Specifying the target reliability levels is one of the key issues in the assessment of existing structures. For a majority of existing buildings and infrastructures, the design life has been reached or will be reached in the near future. These structures need to be reassessed in order to verify their safety. Eurocodes provide a general basis primarily intended for the design of new structures, but the basic principles can be used for assessing existing buildings, too. Reliability levels are generally based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 8 publications
(7 reference statements)
2
49
1
5
Order By: Relevance
“…It is observed that for larger N, the fib bulletin 80 for existing structures requires higher reliability levels than the ISO standard for new structures ('small relative life-saving costs'). This is in contradiction with numerous previous studies advocating lower target levels for existing structures [8,19,[23][24][25] and with the theoretically justified approach to reduce target reliability levels for increasing costs of safety measures. The discrepancy is primarily attributable to the risk-averse value k = 2 adopted in the fib bulletin.…”
Section: Application To a Railway Bridgecontrasting
confidence: 86%
See 2 more Smart Citations
“…It is observed that for larger N, the fib bulletin 80 for existing structures requires higher reliability levels than the ISO standard for new structures ('small relative life-saving costs'). This is in contradiction with numerous previous studies advocating lower target levels for existing structures [8,19,[23][24][25] and with the theoretically justified approach to reduce target reliability levels for increasing costs of safety measures. The discrepancy is primarily attributable to the risk-averse value k = 2 adopted in the fib bulletin.…”
Section: Application To a Railway Bridgecontrasting
confidence: 86%
“…For railway civil engineering structures, it is assumed that this fraction is commonly low (exceptions may include most exposed workers), individual risk criteria become less important and group risk criteria dominate the derivation of target reliability values [7][8][9]. These criteria include human, economic and environmental criteria and are briefly reviewed in the following sections.…”
Section: Classification Of Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety assessment procedure consists in a comparison between the computed and a target reliability index, β target , given in codes or bibliography [3,33].…”
Section: Reliability Analysismentioning
confidence: 99%
“…Las recomendaciones holandesas relativas a las actividades industriales en general distinguen entre requisitos para los sistemas de nueva construcción y existentes, estableciendo unos límites de aceptación, r IR,adm , de 10 -6 y 10 -5 por año, respectivamente [Vrijling 2005]. Otros autores holandeses adoptan este último valor para la determinación de los índices de fiabilidad requeridos para la evaluación de las estructuras existentes [Steenbergen 2010], alineándose con la citada norma suiza destinada a los mismos fines [SIA 269 2011]. Unos desarrollos similares en la República Checa [Sykora 2013], mientras tanto, están basados en un valor r IR,adm = 10 -6 por año, en concordancia con la norma internacional [ISO 2394[ISO 1998.…”
Section: Riesgos Para Las Personasunclassified